A seismic study of lithospheric flexure in the vicinity of Tenerife, Canary Islands - Watts, A; Peirce, C; Collier, J; Dalwood, R; Canales, J; Henstock, T (1997)
Seismic data have been used to determine the crustal and upper mantle structure of Tenerife, Canary Islands, a volcanic island of Tertiary age located on > 140 Ma oceanic crust. Reflection data show that oceanic basement dips gently towards the island, forming a flexural moat which is infilled by 2-3 km of well stratified material. The moat is characterised by a major angular unconformity, which we attribute to volcanic loading of pre-existing oceanic crust and overlying sediments and the subsequent infilling of the flexure by material that was derived, at least in part, from the islands. Refraction data show that the flexed oceanic crust has a mean thickness of 6.41 ± 0.42 km and upper and lower crustal velocities of 4.8-5.4 km s-1 and 6.7-7.3 km s-1 respectively. The flexure, which has been verified by gravity modelling, can be explained by a model in which Tenerife and adjacent islands have loaded a lithosphere with a long-term (> 106 yr) elastic thickness of approximately 20 km. Seismic and gravity data suggest that up to 1.5 × 105 km3 of magmatic material has been added to the surface of the flexed oceanic crust which, assuming an age of 6-16 Ma for the shield building stage on Tenerife, implies a magma generation rate of about 0.006 to 0.02 km3 a-1. This rate is similar to estimates from other African oceanic islands (e.g., Reunion and Cape Verdes), but is significantly less than that which has been calculated at Hawaii. There is no evidence in either the seismic or gravity data that any significant amount of magmatic material has "underplated" the flexed oceanic crust. The crustal and upper mantle structure at Tenerife therefore differs from other oceanic islands such as Hawaii and Marquesas where > 4 km of underplated material have been reported.